Crioglobulinemia esencial. Informe de un caso - Manrique Ugarte , Willard (2024)
The case of a 49 years old man with ulcero necrotic lesions on areas of his body exposed to cold is presented. By inmunoelectrophoretic studies of his plasma and serum kept at 37°C, and of the precipitate and supernatant at 4°C it is concluded that this patient has a cryoglobulin. This cryoglobulin has shown to consist of two paraproteins, IgG type with kappalight chains. Cryofibrinogen has been detected in the precipitate as well. A clinical discussion is made emphazising the nosographic, etiopathogenic and therapeutic implications of the case being published.